2007
DOI: 10.1093/ndt/gfm559
|View full text |Cite
|
Sign up to set email alerts
|

Haemodialysis patients with sleep apnoea syndrome experience increased central adiposity and altered muscular composition and functionality

Abstract: Haemodialysis patients with sleep apnoea syndrome demonstrate poorer functional capacity, physical performance and muscle composition, compared to non-apneic dialysis patients. Overall, sleep apnoea appears to partly contribute to the total diminished functional capacity of haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
1
24
0
2
Order By: Relevance
“…It is well known that several disturbances related to the loss of renal function as well as obesity may affect the pattern of sleep [42,43]. A study using polysomnographic analysis in 43 patients on hemodialysis showed an elevated prevalence of sleep apnea (51.2 %) that was more severe in patients with greater amount of body fat and lower physical capacity [44].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that several disturbances related to the loss of renal function as well as obesity may affect the pattern of sleep [42,43]. A study using polysomnographic analysis in 43 patients on hemodialysis showed an elevated prevalence of sleep apnea (51.2 %) that was more severe in patients with greater amount of body fat and lower physical capacity [44].…”
Section: Discussionmentioning
confidence: 99%
“…Disturbed sleep is reported to be associated with reductions in circulating anabolic hormones [14], [15] thus it could affect muscle metabolism. Indeed, some data indicates that the lack of sleep is associated with reduced muscle size in HD patients [16] and it is plausible that in HD patients with RLS the anabolic effect of sleep might be further reduced. Given that RLS disturbs sleep quality, we hypothesized that this could have a detrimental effect in the HD patient's muscle quantity and/or quality.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the respiratory disturbance index did not correlate with ISI Matsuda ; neither did it differ significantly between the two groups. This result is somehow unexpected since hemodialysis patients with sleep apnea syndrome have reduced functional capacity and altered muscle composition (55), both predisposing to impaired glucose tolerance. It is possible that the longer the patients suffer from sleep disorders, the more insulin resistant they become; however, no such data are yet available for this population of hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, hemodialysis patients also suffer from sleep disorders (46,55) and show increased levels of visceral adiposity and central obesity (43,56). It seems, therefore, that factors involved in the development of IR and glucose intolerance in nonrenal failure populations, are present and might even be compounded under uremic conditions.…”
mentioning
confidence: 99%